Residual Effects of Lime- and Clay-Amended Biosolids Applied to Coarse-Textured Pasture Soil - Sanjutha Shanmugam; Lynette K. Abbott (Applied and Environmental Soil Science)
This study investigated whether there was residual effect of application of lime- and clay-amended biosolids (LaBC®) on ryegrass growth and soil microbial biomass in a coarse-textured, acid pasture soil. Reapplied LaBC® increased fertiliser-use efficiency and plant growth in this glasshouse experiment. Soil management history was established with a single application of LaBC® (50 t ha−1 wet weight equivalent) with or without inorganic fertiliser (NPK) prior to growing annual ryegrass for 5 cycles. In cycle 6 there was no residual nutrient effect of the original application of LaBC® but there was a residual liming effect of the previously applied LaBC®. A nutrient effect of reapplied LaBC® in plant growth cycle 6, had little residual benefit in cycle 7. The residual concentration of inorganic N remaining in this coarse-textured acid soil after a single application of LaBC® was negligible and did not appear to be a risk to the environment when applied at 50 t ha−1 wet weight equivalent.